Experimental study of stainless steel angles and channels in bending. (November 2015) - Theofanous, M.; Liew, A.; Gardner, L.
Abstract: Substantial research has been conducted in recent years into the structural response of stainless steel components, with the focus being primarily on doubly symmetric cross-sections. Limited experimental data exist on non-doubly symmetric stainless steel sections in compression, while there is an absence of such data in bending, despite these sections being widely used in the construction industry as wind posts, lintels and so on. To address this limitation, and to bring an improved understanding of the behaviour of these sections, an experimental study into the flexural response of stainless steel channels bent about their minor axis and angles bent about their stronger geometric axis is described herein. In total, 16 bending tests on austenitic stainless steel beams have been conducted and the obtained results, including the full load-deformation history and observed failure modes have been described. Auxiliary tests on tensile coupons extracted from the tested sections and initial geometric imperfection measurements have also been performed and are reported in detail. The influence of the spread of plasticity and strain hardening on the shift of the neutral axis and the ultimate load carrying capacity is also examined. Based on the obtained test results, the current design provisions of EN 1993-1-4 [1] for these types of cross-sections were assessed and found to be unduly conservative. The effect of strain hardening on the structural response of stocky stainless steel sections and the need to account for it in design has been highlighted.